Molecular and Biochemical Pathways Encompassing Diabetes Mellitus and Dementia - Behl, Tapan; Arora, Arpita; Sehgal, Aayush; Singh, Sukhbir; Sharma, Neelam; Bhatia, Saurabh; Al-Harrasi, Ahmed; Bungau, Simona; Mostafavi, Ebrahim (CNS & Neurological Disorders - Drug Targets, 2022)
Diabetes mellitus is a major metabolic disorder that has now emerged as an epidemic, and it affects the brain through an array of pathways. Patients with diabetes mellitus can develop pathological changes in the brain, which eventually take the shape of mild cognitive impairment, which later progresses to Alzheimer’s disease. A number of preclinical and clinical studies have demonstrated this fact, and molecular pathways, such as amyloidogenesis, oxidative stress, inflammation, and impaired insulin signaling, are found to be identical in diabetes mellitus and dementia. However, the critical player involved in the vicious cycle of diabetes mellitus and dementia is insulin, whose signaling, when impaired in diabetes mellitus (both type 1 and 2), leads to a decline in cognition, although other pathways are also essential contributors. Moreover, it is not only the case that patients with diabetes mellitus indicate cognitive decline at a later stage, but many patients with Alzheimer’s disease also reflect symptoms of diabetes mellitus, thus creating a vicious cycle inculcating a web of complex molecular mechanisms and hence categorizing Alzheimer’s disease as ‘brain diabetes.’ Thus, it is practical to suggest that anti-diabetic drugs are beneficial in Alzheimer’s disease. However, only smaller trials have showcased positive outcomes mainly because of the late onset of therapy. Therefore, it is extremely important to develop more of such molecules that target insulin in patients with dementia along with such methods that diagnose impaired insulin signaling and the associated cognitive decline so that early therapy may be initiated and the progression of the disease can be prevented.
Keywords: forkhead box o (FOXO)